Ruptured Right Cornual Pregnancy - Pokhrel, Shreesiya; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema Kumari; Shrestha, Ranjana; Bhattachan, Kabin; Thapa, Shekhar; Paudel, Rekha; Bajracharya, Nishma (Nepal Journal of Obstetrics and Gynaecology, 2018)
The ectopic implantation is implantation of fertilized ovum outside the uterine cavity, ampulla of fallopian tube being the most common site. A cornual or interstitial pregnancy is an ectopic pregnancy that develops in the interstitial portion of the fallopian tube which is one of the most hazardous type of ectopic gestation. Treatment depends on the week of gestation at the time of diagnosis, level of serum β HCG, findings of ultrasonography, hemodynamic stability of the patient and the choice of future fertility. In this case report, we present a case which was previously misdiagnosed as a case of missed abortion at 8 weeks of gestation by transabdominal ultrasound and patient underwent medical abortion with mefipristione and misoprostolandafter 1 month presented with pain abdomen and was confirmed as extrauterine pregnancy by transabdominal ultrasound followed by surgical management.